FAKTOR KOMPENSASI DAN STRATEGI GOJEK DALAM MENINGKATKAN KEPUASAN KERJA PARA DRIVER - Darma, Gede Sri; Wicaksono, Katon; Sanica, I Gede; Abiyasa, Agus Putu (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
Employees are the main assets of the company that requires the company to be able to create employee satisfaction so as to increase productivity. One strategy to increase power is through compensation. The purpose of this study was to determine the compensation factors and Gojek's strategy in increasing job satisfaction of Gojek drivers. This type of research uses qualitative research. The data source used is primary data. Data collection techniques using observation, interviews and documentation, research subjects and Man-six Go-jek drivers in Denpasar. The results showed the application of compensation with a trip and bonus system, a trip system with a 20% discount for companies, bonus points, daily bonuses. With the current compensation system, drivers are satisfied even without a fixed salary. Gojek's strategy in increasing job satisfaction of gojek drivers is to innovate to improve the system and management by replacing the old system with a rating system.